Edukasi Olahraga dan Gaya Hidup Sehat bagi Siswa dan Guru di SMKS YPK Betlehem Papua - Saharuddin Ita; Sutoro Sutoro; Astini Asri; Ipa Sari Kardi; Muhammad Fitrah Mubarak (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
A healthy lifestyle and regular exercise are important foundations in shaping a high-quality generation, especially in schools. This community service activity aims to increase the knowledge and awareness of students and teachers at SMKS YPK Betlehem, Papua regarding the importance of exercise and a healthy lifestyle. The methods used to carry out this activity include educational lectures, exercise demonstrations, and interactive discussions. Evaluation was conducted through pre-tests and post-tests to measure participants' understanding. The results showed significant improvements in various aspects, with the most dominant improvements occurring in the aspects of the benefits of exercise for mental health (93.88%), knowledge about the benefits of exercise (88.37%), and the dangers of sedentary behaviour (87.76%). Other aspects also experienced positive improvements, namely awareness of the risks of unhealthy lifestyles (84%), strategies for starting and maintaining healthy living habits (83.02%), types of sports and how to do them (79.25%), and motivation to exercise regularly (73.08%). Based on the data analysis results, it was concluded that the average increase was 84.19%. This PKM had a positive impact on improving health literacy among students and teachers at SMKS YPK Betlehem Papua and is expected to stimulate the implementation of a sustainable healthy lifestyle.